Internet Banking Service Quality on Customer Satisfaction Levels PT Bank Mandiri (Persero) Tbk Medan Petisah Branch Office - Bertha Nerphy Siahaan (Cahaya Abadi Publisher, 2024)
The research entitled “The Effect of Internet Banking Service Quality on Customer Satisfaction of PT. Bank Mandiri (Persero) Tbk KCP Medan Petisah